2016
DOI: 10.1186/s12879-016-1532-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of case definitions to detect respiratory syncytial virus infection in hospitalized children below 5 years in Rural Western Kenya, 2009–2013

Abstract: BackgroundIn order to better understand respiratory syncytial virus (RSV) epidemiology and burden in tropical Africa, optimal case definitions for detection of RSV cases need to be identified.MethodsWe used data collected between September 2009 - August 2013 from children aged <5 years hospitalized with acute respiratory Illness at Siaya County Referral Hospital. We evaluated the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of individual signs, symptoms and stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
2
29
1
Order By: Relevance
“…The 47 eligible publications are listed in Table . One quarter of these studies included children aged 0 to 5 years, and 6.4% and 12.8% of studies recruited children aged 0 to 3 years and aged 0 to 2 years, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 47 eligible publications are listed in Table . One quarter of these studies included children aged 0 to 5 years, and 6.4% and 12.8% of studies recruited children aged 0 to 3 years and aged 0 to 2 years, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, 11 studies defined fever as body temperature ≥38°C, 6 studies used cutoff values at 37.5°C, 27,35,37,40,52,65 and 1 study 38.2°C, while 22 studies did not define fever at all. Various clinical data collection methods, including phone interviews questionnaires, and surveys, 70 were used to obtain information on clinical features; clinical data collection for these studies may thus have been subject to recall bias, interviewer bias, or misclassification bias. Additional issues may arise in the design of control groups in observational and cohort studies Among 6 case‐control studies, merely 2 used age‐matched or sex‐matched control groups and 1 was randomized.…”
Section: Discussionmentioning
confidence: 99%
“…The inter‐rater agreement for study selection was high ( κ = 0.81). Finally, 66 full texts including 67 studies were included (one paper included two studies) …”
Section: Resultsmentioning
confidence: 99%
“…The ILI and SARI case definitions were developed for influenza surveillance and may not be optimal for the detection of non-influenza respiratory viruses, including RSV in young infants. 22,23 An additional potential limitation to the detection of respiratory viruses in this surveillance system was the use of throat rather than nasal or nasopharyngeal swabs. A paired comparison of throat and nasopharyngeal swabs in Kenya demonstrated that among SARI patients, throat swabs were less likely than nasopharyngeal swabs to yield influenza B virus, PIV-2 and PIV-3 but more likely to yield adenovirus and influenza A virus.…”
Section: Discussionmentioning
confidence: 99%